Family Caregiver Burden of Elderly with Dementia : A Literature Review - Rakhel Maharani Putri Yusyah Biran; Martyarini Budi Setyawati; Adiratna Sekar Siwi (Universitas Muhammadiyah Surakarta, 2022)
Background: The majority of the elderly with dementia living in a community have received care from family caregivers with curious complexity of problems to be identified during the care at home. Objective: To identify the level of burden and characteristics that affect the burden on family caregivers who care for the elderly with dementia. Method: A literature reviewwith a search for relevant articles was published between 2015-2020 using the four databases PubMed, Google Scholar, DOAJ,and Oxford Academic Journals. The selection protocol used the PRISMA flow diagram by setting inclusion and exclusion criteria with the PEOS framework about family caregiver burden caring for elderly with dementia. Results: Nineteen articles that met the inclusion criteria and were identified in this literature review were found from Asia, Europe, the U.S , and Brazil. Most family caregivers were identified as having a moderate level of caregiving burden that depends on various factors including characteristics of elderly with dementia, sociodemographic characteristics of caregivers, and characteristics of care itself. The presence of behavior problems, neuropsychiatric symptoms and dependence on daily care in elderly with dementia are the main characteristics that predict the burden. Conclusions: The existence of burden during care that tends to increase on family caregivers, makes it necessary to develop a good strategy to minimize the burden in the future by considering the involvement of health professionals in providing appropriate assistance and services.